The Best Common Feature Between ii-Open and α-Open Sets (المجلة الدولية للبحوث العلمية, 2023)
It is well known that for any topological space the family of all open sets is also a topological space. In this paper, we introduce a new description of ii-open sets in a topological space with proof that the family of ii-open sets is again a topological space.